BEST PRACTICE LITERASI DIGITAL NURUL IMAN “LIDI NURIM” - Rahayuningsih; Tauvan Nuswantari (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This best practice was aimed to convey the author's experience in applying digital literacy to create a culture of literacy among students in grades 4, 5 and 6 at SD IT Nurul Iman. The strengthening of character education through a culture of digital literacy among students needed to be developed from an early age. The students who dominate elementary school now are Z generation and alpha generation, they are connected to the digital world in their daily lives. This motivated teachers to continue to transform and innovate so that the learning process is in line with the current generation's times. There are 2 instruments used in this best practice, namely observation sheets and questionnaires. There are two observation sheets, including: (1) Observation sheet to obtain data about the teacher's activities and role in implementing "Lidi Nurim" digital literacy, (2) Observation sheet to obtain data on activities carried out by students during the digital literacy process. Meanwhile, the questionnaire instrument used was a Likert scale questionnaire. This type of measurement scale has a gradation from very positive to very negative. The questionnaire would be used before and after the implementation of digital literacy so that the target's attitudes towards literacy and technology  were known before and after. The validity of the instrument could be reached by carrying out the validity test. The test used expert judgment techniques, the opinion of experts, namely the school principal. Based on the overall results of observations and data analysis, it could be concluded that after implementing digital literacy "Lidi Nurim", the children have a positive culture of liking literacy. Apart from that, the students would be wiser in using technology, especially using smartphones at home. Another accompanying impact was the increase in the score of Indonesian Language and ICT subjects